Communication Managerial Skill For Business Communication On Employee Relations Studies - Yohanes Jefrinus Bessy; Yenny, Yenny; Harliantara, Harliantara; Nur’annafi Farni Syam Maella; Zulaikha, Zulaikha (Jurnal Ekonomi, 2024)
Throughout numerous historical periods, our comprehension of managerial abilities has expanded significantly. In the past, industrial management has primarily concentrated on the maximization of revenue and the resolution of crises, occasionally neglecting the importance of prioritizing the efficacy of human resources within a corporation.Age-based discrimination in the professional sphere in contemporary Indonesia underscores the ongoing challenges of effectively demonstrating managerial skills. Consequently, the persistence of this pattern may still be observed.  This research explores the vital need of good communication abilities for managers in enhancing employee interactions, especially in the Indonesian corporate context. By conducting an extensive analysis of the literature, we have discovered the profound influence that managerial communication has on employee engagement, satisfaction, and the overall efficiency of an organization. Our research highlights the importance of changing managerial practices to focus on effective communication, which will create a more inclusive and productive work environment.